Production of Biodiesel from Coconut Oil Using Microwave: Effect of Some Parameters on Transesterification Reaction by NaOH Catalyst - A. Suryanto; Suprapto Suprapto; Mahfud Mahfud (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The purpose of this research was to study the effect of reaction time and NaOH catalyst in transesterification of coconut oil enhanced by microwave and to obtain a biodiesel. Reaction was conducted in batch reactor which equipped by microwave. Coconut oil contains saturated fatty acids about 70% with medium chain (C8-C14), especially lauric acid and myristic acid. The reaction was initiated by mixing oil and methanol with oil to methanol mole ratios of 1:3, 1:6, 1:9 and 1:12, catalyst concentration of 0.1, 0.15, 0.2, 0.25 and 0.3 wt.%, as well as setting electrical power at 100, 264 and 400 W. The reaction times were of  0.5, 1, 1.5, 2, 2.5, 3 and 3.5 min. The result showed that microwave could be employed as an energy source and was able to accelerate the transesterification process to produce biodiesel using NaOH catalyst. The biodiesel yields increase with increasing microwave power. The highest yield of biodiesel obtained  was of  97.37%  with reaction conditions set at 0.2 wt.% catalyst, a reaction time of 2 min, molar ratio of methanol to oil 1:9 and microwave power of 400 watt. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)